Green synthesized of Fe3O4 nanoparticles and its application in preparation of probiotic Jelly Yogurt - Asmaa G. Abu-El Khair; Hoda S. El-Sayed; Samah M. El-Sayed; Ahmed M. Youssef (Food and Humanity, 2026)

Evaluation of a lipid peroxidation-dependent ferroptosis RNA panel expression as a potential noninvasive biomarker in patients with nonalcoholic steatohepatitis-associated hepatocellular carcinoma - Amr A. El-Sayed; Asmaa I. Nabeel; Marwa G. A. Hegazy; Ali El Anwar; Marwa Matboli (Molecular Biology Reports, 2026)

Comparing the potential efficacy of stromal vascular fraction and adipose mesenchymal stem cell-derived exosomes in a rat model of chromium-induced thyroid dysfunction - Sara Adel Hosny; Asmaa Mohammed ShamsEldeen; Eman Emad Eldin Mohamed; Marwa Alkaffas; Rokia Mohamad Hassan; Seham Mohamed Sayed Mostafa; Hala Hassan Mohamed (Tissue and Cell, 2026)

Impact of ABCB1 (rs1045642) polymorphism on antipsychotic-induced extrapyramidal symptoms in Egyptian patients with schizophrenia - Asmaa Mohamed Sayed Ahmed; Asmaa Mohammad Moawad; Mennat-Allah Tarek; Marwa Abdelgwad; Alaa Mohamed Ibrahim Aboutaleb; Abrar Roshdy Abouelkheir (Food and Chemical Toxicology, 2026)

Gamma Radiation–Induced Synthesis of Pectin/Arabic Gum-Based Nanocomposite Hydrogels for Enhanced Water Remediation - Asmaa Sayed; D. M. Aboelkhir; Razan Mohamed; Ayman Amin; Ghada A. Mahmoud (Water, Air, & Soil Pollution, 2026)

Plant-derived natural products against hepatocellular carcinoma: chemical diversity, mechanisms of action, and organ-based classification - Nourhan Hisham Shady; Aliaa Gamal; Asmaa Emad Fekry; Amna Mahmoud Sayed; Zaki Ebrahim Afify; Ziad Abdellah Mohamed; Ingy M. Hashad; Mohammed I. Rushdi; Ahmed Zayed; Usama Ramadan Abdelmohsen (Natural Product Research, 2026)

The protective effects of chrysin-loaded casein nanoparticles on rabbit sperm following cryopreservation: Antioxidant and anti-apoptotic insights - Elsayed S.I. Mohammed; Mohamed Shawky El Sayed; Mohamed Ashour; Michelyn Haroun; Roshmon Thomas Mathew; Ramya Ahmad Sindi; Nawal Al-Hoshani; Sameh A. Abdelnour; Asmaa Sheiha (Tissue and Cell, 2026)

Artificial spawning of African catfish (Clarias gariepinus) with different forms and sources of pituitary gland extract: influence on fecundity, sex hormones, and reproductive performance - Hala S. Khalil; Hamed H.E. Saleh; El-Sayed I. Attia; Asmaa M. El-Agri; Fatma Ragab Abouel Azm; Gad H.G. Hussein; Rasha K. Abdel-Wahed (Frontiers in Marine Science, 2026)
Introduction The investigation was performed to compare the influence of using different pituitary gland extract types (dried and fresh) from common carp ( Cyprinus carpio ) and African catfish ( Clarias gariepinus ) on fecundity, sex hormones, and artificial spawning performance of African catfish. Methods Pituitary glands were collected from sixty-four male catfish and sixty-four carp broodstocks to formulate four treatments: dried catfish pituitary gland extract (DPG catfish ), fresh catfish pituitary gland extract (FPG catfish ), dried carp pituitary gland extract (DPG carp ), and fresh carp pituitary gland extract (FPG carp ). Sixteen ripe females (920 to 1190 g) and sixteen ripe males (1060 to 1150 g) with a sex ratio (1:1 male ♂: female ♀) were chosen for each treatment. Results and discussion The highest fecundity and reproductive performance were observed in the DPG catfish -treated group, followed by the DPG carp -treated group. The latency periods were recorded as 12 h for DPG catfish , 17 h for FPG catfish , 12.5 h for DPG carp , and 21 h for FPG carp . DPG catfish treatment significantly improved (P ≤ 0.05) ovulation performance, reproductive output, fertilization and hatching success, and circulating estrogen, progesterone, and testosterone levels. In contrast, both fresh pituitary treatments (catfish and carp) resulted in noticeably lower outcomes. The results indicate that DPG catfish extract consistently outperformed other treatments across all measured spawning parameters, suggesting its effectiveness in enhancing seed production in African catfish aquaculture.

The possible effects of folic acid and postbiotic yeast on doxorubicin–induced cardiotoxicity in rats: interactions among the gut microbiota, antioxidants, and NLrp3 activities - Heba M. Galal; Marwa H. Bakr; Dalia A. Elgamal; Nahla M. Elsherbiny; Doaa M. Raafat; Asmaa M. Ismail; Sally A. Sayed (Journal of Molecular Histology, 2026)

Green biocatalysis: Box–Behnken-optimized cellulase from thermophilic Streptomyces griseorubens NBR14 for waste management and dye removal - Abd El-Rahman Fathy Gomaa; Sheng Qin; Mohamed H. El-Sayed; Asmaa M. M. Mawad (Biodegradation, 2026)

Sustainable harnessing of Red Sea brown seaweed extracts as plant growth promoters: Analytical profiling and application to faba bean - Mohammed Rawway; Asmaa Sayed Abdelgeliel; Reem Hasan Obaydo; Maged Fouda; Mohamed Hamza; Mohammed Ezzeldien; Eman A. Alwaleed (South African Journal of Botany, 2026)

Correction to: Spatial Distribution of Polychlorinated Biphenyls in Some Watercourses: A Study on Water Quality, Risk, and Effect on Macroinvertebrates - Sara S. M. Sayed; Rania M. Abd El‑Hamid; Naglaa Zanaty; Asmaa Abdel‑Motleb (Water, Air, & Soil Pollution, 2026)

New bioactive mono-acyl glycerol ester from the Red Sea marine coral Sclerophytum levi - Basma H. Farouk; Asmaa M. Abdel-Tawab; Mohamed E. Mostafa; Fawzia Z. El-Ablack; El Sayed A. E. Hamed; Seif-Eldin N. Ayyad (Natural Product Research, 2026)

Prenatal exposure to the fungicide flutolanil induces developmental and hepatic toxicity in pregnant rats and their fetuses: Insights from In Vivo and In Silico studies and the protective role of Chlorella vulgaris - Samah S. Arafa; Mohammed Adel; Osman F. Abdelzaher; Sultan A. Alfawaz; Nermeen M. Nooreldien; Ruaa Yasir Altayeb Mohamed; Asmaa M. Abd El-Azez; Hanaa A. Abd El-Gawwad; Salah M. EL-Sharkawy; Eman Sweed; Shimaa Abdelsattar; Asmaa A. EL-Dahshan; et al. (Reproductive Toxicology, 2026)

Highly sensitive colorimetric 3D covalent organic framework sensors with artificial intelligence analysis enabled early detection of plant diseases - Asmaa Gbiliy; Ibrahim Senosy; Marwa A.A. Saadan; Mahmoud Sayed; I.P.W.A.V. Kumara; Ge-Fei Hao; Man-Qun Wang (Chemical Engineering Journal, 2026)

Efficient biofuel production from waste cooking oil using Pt/ZSM-5 catalysts derived from rice husk and aluminum foil - Osama Saber; Adil Alshoaibi; Nagih M. Shaalan; M.A. Sayed; Asmaa S. Morshedy (Biomass and Bioenergy, 2026)

Guava leaf (Psidium guajava) byproducts in animal and fish diets: a review of health benefits, immunomodulation, and sustainable applications - Khaled M. Al-Marakby; Islam G. Abdelghani; Ehab El-Haroun; Zeinab Mahasneh; Roshmon Thomas Mathew; Asmaa M. Sheiha; Mohamed F. Abo El-Maati; El-Sayed Hemdan Eissa; Md Altafur Rahman; Sameh A. Abdelnour (Tropical Animal Health and Production, 2026)

Pimenta racemosa extract ameliorates chemically induced ulcerative colitis in rats by suppressing inflammation and oxidative stress - Haitham A. Ibrahim; Fathia S. Elshaarawy; Mohamed I. S. Abd-elhady; Wafaa Hamdy; Merhan E. Ali; Asmaa A. Ahmed; Elsayed K. El-Sayed (Inflammopharmacology, 2026)
Pimenta racemosa ( P. racemosa ) tree leaves are used in traditional medicine to alleviate flatulence and gastrointestinal disorders. Ulcerative colitis (UC) is a gastrointestinal inflammatory disease with well-known inflammatory and immunoregulatory pathological features. The complexity of the disease requires multi-targeted treatment. Because of their relative safety and effectiveness, natural products can be utilized as adjunct and alternative agents to conventional UC treatment. So , the present work aimed to isolate phenolic constituents of the plant’s 80% aqueous methanol extract (AME) and evaluate its protective effect on acetic acid-induced ulcerative colitis (UC) in rats. The defatted AME was chromatographed, and structures of the isolated compounds were elucidated using UV, NMR spectroscopy and HPLC–ESI–MS analysis. Induction of ulcerative colitis was done using Acetic acid, the protective effect against ulcerative colitis was supported by histopathological and immunohistochemical examinations. The isolated compounds are Kaempferol 3- O - β -D-glucopyranoside (kaempferol 3- O -glucoside) or (Astragalin) (1) , quercetin 3- O-β -D-glucopyranoside (Isoquercetrin) (2) , Quercetin (3) , Catechin (4) , quercetin 3- O-α- L-rhamnospyranoside (Quercetrin) (5) . The AME of P. racemosa significantly alleviated the UC by decreasing the disease activity index and Wallace score. Additionally, GSH, CAT, and SOD were increased, and MDA was decreased, suggesting AME’s antioxidant activity. The decreased levels of WBCs, neutrophils, TNF-α, IL-1β, IL-6, MPO, and NF-κB p65 support the AME’s anti-inflammatory properties. The highest activity was recorded for the dose of 1000 mg/kg. These findings were in harmony with the histopathological examination and the Alcian Blue staining for mucin content. The current study revealed that the AME of P. racemosa has protective activities against UC in rats via its antioxidant and anti-inflammatory properties may be attributed to its phenolic profile.

Jojoba Oil Protects against Chlorpyrifos-Induced Testicular Toxicity by Modulating Notch1/Jagged1-Inflammatory Axis and Oxidative Stress - RHM Salama; Asmaa A. Abdullah; Sary Kh. Abd-elghaffar; O A Sayed; Nashwa Maghraby (Cell Biochemistry and Biophysics, 2026)

Nanocapsule-based vitamin B12 as a novel strategy against vancomycin-induced nephrotoxicity: Targeting oxidative stress, ER stress, inflammation, and fibrosis in rats - Mahran Mohamed Abd El-Emam; Maha S. Kilany; Mohamed Ibrahim; Milad Reda Qelliny; Mahmoud Mostafa; Marwa Mohamed El Sayed; Tarek khamis; Rasha Ahmed Ahmed Agaga; Asmaa Monir Eltaweel; Mohamed Fouad Mansour (Toxicology and Applied Pharmacology, 2026)

Oil sludge from an environmentally hazardous pollutant to an efficient source for energy production via thermal/ catalytic pyrolysis routes - Mohamed N.A. Mahmoud; Esraa M. El-Fawal; Ahmed M.A. El Naggar; Asmaa I. Zahran; Hussien A. El Sayed; Islam M. El-Sewify; Bassem H. Heakal; Mostafa M.H. Khalil (Fuel, 2026)

Spatial Distribution of Polychlorinated Biphenyls in Some Watercourses: A Study on Water Quality, Risk, and Effect on Macroinvertebrates - Sara S. M. Sayed; Rania M. Abd El-Hamid; Naglaa Zanaty; Asmaa Abdel-Motleb (Water, Air, & Soil Pollution, 2026)
Continued monitoring of polychlorinated biphenyl (PCB) residues in inland watercourses contributes indirectly to Sustainable Development Goal 14 by preserving aquatic biodiversity and ecosystems. Therefore, the current work aims to monitor PCBs in water courses of Giza, Al-Qaliobiah, and Al-Gharbiah Egyptian Governorates and assess their risk using various tools. The highest water temperature was 32.2 °C et al.-Gharbiah during spring. pH values were natural throughout all seasons and sites, except Al-Qaliobiah, which showed alkaline water in the summer. Giza showed high DO in winter (7.75 mg/L), while Al-Qaliobiah and Al-Gharbiah peaked in autumn (5.04 and 6.41 mg/L, respectively). Six PCB congeners (52, 70, 101, 118, 138, and 180) were detected, and their levels exceeded the permissible limit in surface water. PCB-52 and 70 were the most dominant in all investigated governorates. The highest total PCBs were 126.10 and 132.40 µg/L in deep water at Giza and Al-Gharbiah, respectively, while in surface water et al.-Qaliobiah it was 111.90 µg/L. Most PCB congeners were lowest in winter, compared to spring and autumn, and this was inversely proportional to abundance of macroinvertebrates. Hilsenhoff Biotic Index (HBI) values showed relatively poor water quality, indicating significant organic pollution. All hazard quotient (HQ) values were greater than 1, and the carcinogenic risks exceeded the acceptable limits. Therefore, implementing monitoring programs and regulatory policies is vital to protect aquatic ecosystems and public health.

Amelioration of intestinal ischemia reperfusion injury by diacerein via regulation of inflammasome/caspase-1/IL-1β and Wnt/β-catenin pathways in juvenile rats - Marwa Monier Mahmoud Refaie; Nada Amgad Mohamed Abdel Majeed; Sayed Shehata; Asmaa A. Muhammed; Salma M. Hassan; Hoda S. Sherkawy; Fatma F. Ali; Mohamed Rabie Saad; Mousa Mohsen; Shereen Mohammed Mohammed Elsaghir; Enas Fathy; Olivia N. Beshay (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Intestinal ischemia reperfusion (II/R) is an abdominal critical case especially in neonates and during childhood affecting not only the intestinal tissue but also it could damage other remote organs including cardiac tissue even following surgical intervention. Immune homeostasis during II/R has a major role in controlling its progression. Thus, finding additive medical treatment besides the surgical one becomes an urgent need to keep the tissue. So that, we aimed to evaluate the possible ameliorative effect of diacerein (DIA) on II/R-induced injury in juvenile rats. Forty juvenile rats of Wistar albino species were randomly allocated into four different groups: sham group, DIA given group, II/R group via clamping superior mesenteric artery, DIA-treated group (50 mg/kg) with induction of II/R. Data of current model revealed a significant elevation of the measured cardiac enzymes, cleaved caspase-3, and nuclear factor kappa β (NF-κB) in the untreated ischemic group with disturbed oxidative stress parameters, accompanied with dysregulation of inflammasome/caspase-1/IL-1β and Wnt/β-catenin signaling cascades. Fortunately, upon co-administration of DIA, there is a significant decrease of cardiac enzymes, cleaved caspase-3, and NF-κB with normalization of oxidative stress parameters and regulation of inflammasome/caspase-1/IL-1β and Wnt/β-catenin pathways confirmed by marked mitigation of the histopathological changes. This effect of DIA is greatly attributed to its pharmacological properties including IL-1β antagonist effect, anti-oxidant, anti-apoptotic, and anti-inflammatory properties. Thus, DIA could be considered as an adjuvant future medical therapy for those cases of II/R. Graphical abstract

Guar gum-based systems formulated with encapsulated propolis extract for minimally processed fruits and confectionery packaging - Rowaida K. Khalil; Nadeen B. El-Sayed; Rawan H. El-sayed; Rahma M. Sallam; Asmaa Y. Abdelnabi; Nouran S. Soliman; Rawan A. Ibrahim; Menna-tallah A. Ibrahim; Muhammed R. Sharaby; Dalia S. Abdelrahim (Food Hydrocolloids, 2025)

Reprogramming the hepatic immune microenvironment with mirtazapine in early neoplastic transformation: Evidence from a diethylnitrosamine-induced rat model - Elsayed A. Elmorsy; Sameh Saber; Ahmad H. Alhowail; Abousree T. Ellethy; Enas A. Mohamed; Hamad Alsaykhan; Hatim Y. Alharbi; Omar Almansour; Abdelrahman El-Sayed; Manal Mohamed Hatem; Ahmed Kaid Alantry; Walaa A. Allam; et al. (Chemico-Biological Interactions, 2025)

Lycopene alleviates cognitive dysfunctions in an Alzheimer's disease rat model via suppressing the oxidative and neuroinflammatory signaling - Sara El-Sayed El-kazaz; Mona Hafez Hafez; Ahmed E. Noreldin; Asmaa F. Khafaga (Tissue and Cell, 2025)

Chitosan-Nanoparticles Mitigate Cadmium Chloride Hepatorenal Toxicity in BALB/C Mice Via Amendment of Nrf2/HO-1 and NF-κB/iNOS Signaling Pathways - Asmaa F. A. Dawood; Salwa A. Fouad; Hanan M. Alharbi; Mohamed Abd El-Aal; Mohammed I. Elkhateeb; Zain El Abdeen Ali; Nermeen N. Welson; Leila H. Sayed (Biological Trace Element Research, 2025)

Promising role of dietary microalgae blend in alleviating the heat stress draw backs in broiler chickens: Impact on performance, meat antioxidants and fatty acids content and expression of heat shock protein and sirtuins related genes - Doaa Ibrahim; Mohamed Shawky; Asmaa EL- Sayed Kamel; Ahmed Abdelfattah-Hassan; Rahma Taha; Samah S. Khalil; Mohamed Tharwat Elabbasy; Asmaa T.Y. Kishawy (Journal of Thermal Biology, 2025)

Rutin-Loaded Nanocapsules Mitigate Vancomycin-Induced Hepatotoxicity: Development, Characterization, Optimization, and In Vivo Evaluation - Mohamed Ibrahim; Mohamed Fouad Mansour; Mahran Mohamed Abd El-Emam; Tarek khamis; Maha S. Kilany; Amira Ebrahim Alsemeh; Asmaa Monir Eltaweel; Milad Reda Qelliny; Mahmoud Mostafa; Marwa Mohamed El Sayed (Journal of Pharmaceutical Innovation, 2025)
Background Vancomycin (VCM)-induced hepatotoxicity is a significant clinical concern due to its association with oxidative stress, apoptosis, and inflammatory responses. This study investigated the formulation and potential preclinical application of rutin-loaded nanocapsules (RUT-NC) as a hepatoprotective agent against VCM-induced liver injury. Methods Hepatotoxicity was induced in rats through VCM administration, followed by oral treatment with RUT-NC. Liver function, oxidative stress markers, apoptotic proteins, lipid metabolism regulators, and inflammatory cytokines were subsequently evaluated. Results RUT-NC treatment significantly improved liver function parameters, attenuated oxidative stress, and modulated apoptotic pathways by downregulating the expression of p38 , p53 , caspase-8 , miR-122 , miR-7 , and beclin-1. Furthermore, RUT-NC restored lipid metabolism homeostasis by regulating the expression of PPAR-α, FASN, and SREBP-1. Notably, it exerted potent anti-inflammatory effects by suppressing NF-κB , TNF-α , IL-1β , IL-6 , IL-17 , and Gasdermin-D , thereby mitigating chronic liver inflammation. The pathological effects of VCM administration on hepatocytes were effectively counteracted by RUT-NC. Conclusion RUT-NC demonstrates promising hepatoprotective properties by enhancing antioxidant defenses, inhibiting apoptosis, regulating lipid metabolism, and reducing inflammation. These findings highlight its potential as a therapeutic intervention for drug-induced liver injury (DILI) and warrant further investigation for clinical application.

Whole genome sequencing identifies monogenic disease in 56.1% of families with early-onset steroid-resistant nephrotic syndrome - Neveen A. Soliman; Mohamed A. Elmonem; Ahmed F. El-Sayed; Eman Ramadan; Ahmed M. Badr; Fatma M. Atia; Rasha Helmy; May O. Amer; Ahmed Abd El-Raouf; Fadya M. El-Garhy; Omnia M. Abdel-Haseb; Tokka M. Hassan; et al. (Human Genetics, 2025)
Genetic causes of steroid-resistant-nephrotic-syndrome (SRNS) represent a rapidly growing number of monogenic diseases. The reported diagnostic yield of various studies applying genetic panels and exome-sequencing to diagnose SRNS is usually < 30%. We performed genome-sequencing in a cohort of Egyptian SRNS patients. We recruited 47 SRNS patients belonging to 41 unrelated families [28 males/19 females; median (range): 6 (0.5–22 years)]. We established a pipeline for genome sequencing, bioinformatics analysis, variant curation and protein modeling at the Egypt Center for Research and Regenerative Medicine (ECRRM). Disease-causing variants were detected in 27/47 patients (57.4%) belonging to 23/41 families (56.1%), including nine novel variants in NPHS1, NPHS2, COL4A3, MYO1E, NUP93, PLCE1, PODXL, SMARCAL1 and WT1 . Novel variants were confirmed by Sanger sequencing and were segregated in families of affected patients. NPHS2 was the most common causative gene in 8/23 (34.8%) of confirmed families, followed by NPHS1 , WT1 , and SMARCAL1 in 2/23 families (8.7%) each. All detected missense variants were evaluated through protein modeling and were predicted deleterious. Our study expanded the spectrum of SRNS disease-causing variants and revealed a monogenic cause in 56.1% of investigated families. In our cohort, no deep intronic or regulatory variants were detected by genome-sequencing. Pursuing genetic diagnosis in SRNS patients is crucial to inform clinical decision making, genetic counseling, transplantation strategy and prenatal diagnosis thus improving clinical outcome of affected patients.

Biological Diversity Associated with Pesticides Residues in Certain Egyptian Watercourses - Asmaa Abdel-Motleb; Rania M. Abd El-Hamid; Sara S. M. Sayed (Archives of Environmental Contamination and Toxicology, 2025)
The aquatic environment has been contaminated by pyrethroids and triazole pesticide applications, which pose serious health risks to the aquatic ecosystem and human beings. Therefore, the current study aims to evaluate water quality parameters, fungal diversity, and distribution of snails and aquatic plants of certain Egyptian water courses contaminated with pyrethroids and triazole pesticides. Seasonal samples were taken throughout 2021 from different water courses at Giza Governorate and Tanta (Gharbeya Governorate). Qualitative and quantitative surveys showed significant differences in water physical parameters between the two investigated governorates. Deltamethrin, permethrin, Es-fenvalerate, and lambada-cyhalothrin showed the highest pyrethroids concentrations, while tebuconazole, tetraconazole, and difenoconazole were the highest triazole concentrations. Fungal diversity displayed 21 molecularly identified fungal species related to four fungal genera: Aspergillus, Fusarium , Penicillium, and Trichoderma . Penicillium sp. and Aspergillus niger were the most frequent species. Snail diversity recorded 10 and 9 species in Giza and Tanta, respectively. Physa acuta was the most abundant snail. Ten species of aquatic plants were observed in Giza, while six species were observed in Tanta. Specifically, Eichhornia crassipes and Lemna gibba were the dominant species in the two governorates, with the relative abundance (39 and 22%) in Giza and (27 and 23%) in Tanta, respectively. Water quality parameters and seasonal variations could control fungal diversity, snails, and aquatic plant distribution. Different relations between pesticides and biological communities may reflect the ability/inability of certain snails and fungi species to commensalism with pesticide concentrations. Continuous pesticide monitoring is essential for life below water and aligns with SDG14.

Decorin alleviates non-alcoholic fatty liver disease in rats with polycystic ovary syndrome - Hany A. Elkattawy; Amira Ebrahim Alsemeh; Lashin Saad Ali; Mona Mostafa Ahmed; Asmaa Monir Eltaweel; Farha M. Shaikh; Ahmed Behiry; Ahmed El-Sayed Hassan; Deema Kamal Sabir; Dalia Mahmoud Abdelmonem Elsherbini; Sahar K. Ali; Madaniah Omar Zakari; et al. (Tissue and Cell, 2025)

Herbal remedies for oral and dental health: a comprehensive review of their multifaceted mechanisms including antimicrobial, anti-inflammatory, and antioxidant pathways - Mohamed A. Anwar; Ghadir A. Sayed; Dina M. Hal; Mohamed S. Abd El Hafeez; Abdel-Aziz S. Shatat; Aya Salman; Nehal M. Eisa; Asmaa Ramadan; Riham A. El-Shiekh; Shymaa Hatem; Shaza H. Aly (Inflammopharmacology, 2025)
Across diverse cultures, herbal remedies have been used to alleviate oral discomfort and maintain dental hygiene. This review presents studies on herbal remedies with remarkable antimicrobial, anti-inflammatory, antioxidant, anticancer, anticaries, analgesic, and healing properties. The manuscripts demonstrate the depth of scientific inquiry into herbal remedies used for the management of various oral and dental health conditions. These include gingivitis, oral ulcers, mucositis, periodontitis, oral pathogens, carcinoma, xerostomia, and dental caries. Researchers have investigated the phytochemical and pharmacological properties of plant-derived compounds and their extracts evaluated their interactions with oral pathogens and inflammatory processes. The convergence of traditional knowledge and rigorous scientific investigation offers a compelling narrative, fostering a deeper understanding of herbal remedies as viable alternatives to conventional dental interventions. This work has the potential to provide patients with access to gentle, yet effective solutions, and simultaneously offer dental health professionals the opportunity to enrich their knowledge, and ability to provide personalized, holistic care. This review highlights the symbiotic relationship between herbal medicine and scientific understanding, emphasizing the importance of disseminating this knowledge to benefit both practitioners and patients, enabling evidence-based decision-making in dental care. The exploration of herbal remedies offers a promising alternative, potentially mitigating some of these side effects while promoting oral health in a more natural and holistic manner.

Enhancing Patient Outcomes Through Integrated Education and Navigation Programs at the Breast Cancer Comprehensive Center, National Cancer Institute, Cairo University - Emad Shash; Fatma Bektash; Mona Elhosary; Ghada Emam; Asmaa El-Sayed; Dalia Abdelmenam; Rania Abdulmonem A. L. Najar; Reem Eid (Journal of Cancer Education, 2025)

Cytotoxic evaluation of new polyhydroxylated steroids from the Red Sea soft coral Litophyton mollis (Macfadyen, 1936) - Ahmed H. Eissa; Asmaa M. Abdel-Tawab; El Sayed A.E. Hamed; Fawzia Z. El-Ablack; Seif-Eldin N. Ayyad (Natural Product Research, 2024)

The pyrolytic distillation of waste lubricants with waste oilfield scale into value-added fuel - Sayed K. Attia; Ahmed M. Rashad; Mohamed Mohamady Ghobashy; Asmaa. E. Elsayed; Doaa I. Osman (Fuel, 2024)

Biosynthesis of Silver, Copper, and Their Bi-metallic Combination of Nanocomposites by Staphylococcus aureus: Their Antimicrobial, Anticancer Activity, and Cytotoxicity Effect - Mohsen A. Sayed; Tahany M. A. Abd El-Rahman; H. K. Abdelsalam; Sayed M. S. Abo El-Souad; Rawan Muhammad Shady; Radwa Abdallnasser Amen; Mostafa Ahmed Zaki; Martina Mohsen; Sara Desouky; Samar Saeed; Seif Omar; Asmaa A. H. El-Bassuony (Indian Journal of Microbiology, 2024)
The present study outlines an easy, cheap, and environmentally friendly way to make Staphylococcus aureus -mediated bimetallic silver-copper nanocomposites (Ag/Cu) that can fight cancer and germs. The gram-positive S. aureus synthesized Ag, Cu, and their bi-metallic nanocomposites extracellularly. We aimed to prepare the bimetallic nanocomposite in two different ways, and we compared them in terms of characterization and biological applications. The first one is a bimetallic nanocomposite (Ag/Cu b ) that was made by mixing Ag and Cu metal ions in equal amounts (50:50). Then, the whole mixture was reduced. The second is the after-reduction bimetallic nanocomposite (Ag/Cu a ), in which each metal ion was reduced separately, and then the nanocomposites were mixed (50:50%) during biological applications. Nanocomposites were characterized using UV–visible spectrophotometry, Fourier-transform infrared spectroscopy, dynamic light scattering, and transmission electron microscopy. The results demonstrated that surface plasmon bands were at 320 nm for Ag NPs and 525 nm for Cu NPs, and a shift from these peaks was observed at 290 nm in the Ag/Cu b bimetallic nanocomposite. The synthesized nanocomposites were confirmed to be in the nanoscale with 20, 40, and 80 nm spherical crystals, respectively. Nanocomposites were assayed for their antimicrobial activity against the gram-negative Pseudomonas aeruginosa , the acid-fast Mycobacterium smegmatis , the gram-positive Bacillus cereus, and S. aureus, in addition to three fungal species, which were Aspergillus flavus , A. fumigatus, and Candida albicans . The minimum inhibitory concentration and minimum bactericidal concentration were determined. The Ag/Cua/Cuaetallic nanocomposite was the most potent antimicrobial compound. The anticancer activity of the tested compounds was assayed against the hepatocellular carcinoma cell line (HepG-2). Low cytotoxic activity was recorded in most assayed nanocomposites against the baby hamster kidney cell line (BHK).

Phytochemical profiling of Ananas comosus fruit via UPLC-MS and its anti-inflammatory and anti-arthritic activities: In Silico, In Vitro and In Vivo Approach - Sally E. Khaled; Faten Mohamed Ibrahim; Eman Abdelsalam; Kawkab A. Ahmed; Asmaa K. Al-Mokaddem; Wedian El Sayed Ashour; Amany A. Sleem; Reda Sayed Mohammed (Biocatalysis and Agricultural Biotechnology, 2024)

Automatic Building Extraction from Multispectral LiDAR Using Novel 3D Spatial Indices and Deep Learning Point CNN - Asmaa A. Mandouh; Mahmoud El Nokrashy O. Ali; Mostafa H. A. Mohamed; Lamyaa Gamal E. L.-Deen Taha; Sayed A. Mohamed (Journal of the Indian Society of Remote Sensing, 2024)

Alpha-Asarone attenuates alcohol-induced hepatotoxicity in a murine model by ameliorating oxidative stress, inflammation, and modulating apoptotic-Autophagic cell death - Nada A.M. Ali; Amir Mohamed Abdelhamid; Norhan M. El-Sayed; Asmaa Radwan (Toxicology and Applied Pharmacology, 2024)

Cardioprotective role of diacerein in diabetic cardiomyopathy via modulation of inflammasome/caspase1/interleukin1β pathway in juvenile rats - Marwa M. M. Refaie; Hanaa Hassanein Mohammed; Elshymaa A. Abdel-Hakeem; Asmaa M.A. Bayoumi; Zamzam Hassan Mohamed; Sayed Shehata (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Diabetes mellitus is a common metabolic disorder affecting different body organs; one of its serious complications is diabetic cardiomyopathy (DCM). Thus, finding more cardiopreserving agents to protect the heart against such illness is a critical task. For the first time, we planned to study the suspected role of diacerein (DIA) in ameliorating DCM in juvenile rats and explore different mechanisms mediating its effect including inflammasome/caspase1/interleukin1β pathway. Four-week-aged juvenile rats were randomly divided into groups; the control group, diacerein group, diabetic group, and diabetic-treated group. Streptozotocin (45 mg/kg) single intraperitoneal (i.p.) dose was administered for induction of type 1 diabetes on the 1st day which was confirmed by detecting blood glucose level. DIA was given in a dose of 50 mg/kg/day for 6 weeks to diabetic and non-diabetic rats, then we evaluated different inflammatory, apoptotic, and oxidative stress parameters. Induction of DCM succeeded as there were significant increases in cardiac enzymes, heart weights, fasting blood glucose level (FBG), and glycosylated hemoglobin (HbA1c) associated with elevated blood pressure (BP), histopathological changes, and increased caspase 3 immunoexpression. Furthermore, there was an increase of malondialdehyde (MDA), inflammasome, caspase1, angiotensin II, nuclear factor kappa-B (NF-κB), tumor necrosis factor-α (TNFα), and interleukin 1β (IL1β). However, antioxidant parameters such as reduced glutathione (GSH) and total antioxidant capacity (TAC) significantly declined. Fortunately, DIA reversed the diabetic cardiomyopathy changes mostly due to the observed anti-inflammatory, antioxidant, and anti-apoptotic properties with regulation of blood glucose level.DIA has an ability to regulate DCM-associated biochemical and histopathological disturbances.

As healthy as invasive: Charybdis natator shell extract reveals beneficial metabolites with promising antioxidant and anti-inflammatory potentials - Asmaa Galal-Khallaf; Esraa Samir Aboali; Sobhy El-Sayed Hassab El-Nabi; Ahmed I. El-Tantawy; Eric J. Schott; Khaled Mohammed-Geba (Frontiers in Marine Science, 2024)
Crabs of the genus Charybdis are some of the world’s most aggressive and voracious marine invasive crustaceans. They are found in a wide variety of ecosystems in the Red Sea. Their near ubiquity in diverse marine habitats, however, makes them a possible resource for novel marine-derived bioactive products. To provide an important insight into the potential for C. natator as a beneficial product, its shell methanolic extract was chromatographically analyzed for identification of potential bioactive ingredients. Additionally, two different doses, i.e. a low and a high dose, of this extract were tested for their ability to protect against copper-induced oxidative stress and proinflammatory response in adult zebrafish Danio rerio . Gene expression levels of transcripts of proinflammatory mediators, i.e. nf-κβ and tnf-α ; antioxidant enzymes, i.e. sod , cat , and gpx ; and lipid-metabolizing enzymes, i.e., acox1 and fasn , were determined. The results showed that C. natator shell is rich in potential bioactive metabolites, including diverse unsaturated fatty acids, alkanes, flavonoids, and phenolic acids. Most antioxidant and proinflammatory transcripts in the protected groups were restored to levels that were lower than those in the CuSO 4 -stressed group. The low dose showed special success in inducing these effects. Also, the low-dose-protected group showed significantly elevated acox1 and decreased fasn , suggesting the capability of crab shell extract at a low dose to assist lipolysis and inhibit lipogenesis. The abundant presence of saturated fatty acids in the shell extract can be the reason for the inadequacy of the high dose to promote the antioxidant and anti-inflammatory activities. These results suggest that there is a potential to develop therapeutic industrial uses for C. natator shell, instead of considering it as a discard. Its wealth of bioactive metabolites may contribute to the market for natural products to combat inflammatory and oxidative stress, the origin of many diseases in the modern world.

Immunomodulatory and antioxidant properties of Sarcophaga argyrostoma larval hemolymph: utilizing the Biomphalaria alexandrina snail as a model - Alya Mashaal; Asmaa A. Abo Elqasem; Lina A. Abou El-Khashab; Hend M. El-Menyawy; Basma M. Abou El-Nour; Eman M. Abdullah; Asmaa M. Abdalkareem; Rawda A. Al-gebaly; Asmaa M. El-sayed; Ghada R. Mabrok; Rawda R. Mahmoud; Dina A. Ali; et al. (Biologia, 2024)
In recent years, there has been a growing interest in exploring novel natural sources for antioxidant and anti-inflammatory agents, driven by the need for alternative therapeutic strategies with fewer side effects. This study investigates the potential of the Biomphalaria alexandrina snail as a valuable model organism to evaluate the antioxidant and anti-inflammatory properties of Sarcophaga argyrostoma larval hemolymph. The choice of B. alexandrina snails as a model is based on its ecological relevance and physiological similarities to other organisms, supporting well-established use in ecological and physiological research, as well as it provides a valuable platform for such investigations. Ultimately, this study may open avenues for the development of innovative and sustainable therapeutic interventions rooted in the rich biodiversity of the natural world. The experimental design involves the extraction of hemolymph from S. argyrostoma larvae, followed by a comprehensive analysis of its antioxidant capacity and anti-inflammatory effects using adult snails. Various biochemical assays, including total antioxidant capacity, immunomodulatory markers and histological investigation, will be employed to assess the bioactive potential of the hemolymph. The outcomes of this research can be attributed to the identification of the anti-oxidant and anti-inflammatory effects of hemolymph. This effect was observed through the reduction of oxidative stress and proinflammatory mediators, impacting the biological activities of the snails. The study is the first to shed light on the potential benefits of S. argyrostoma larval hemolymph using an animal model, showcasing its ability to mitigate oxidative and inflammatory responses within the biological context of the snails.

Impact of L-Arginine on diabetes-induced neuropathy and myopathy: Roles of PAI-1, Irisin, oxidative stress, NF-κβ, autophagy and microRNA-29a - Heba M. Galal; Alaa T. Abdelhafez; Manal M. Sayed; Walaa M.S. Gomaa; Tohamy Anwar Tohamy; Asmaa M.S. Gomaa; Tarek H. El-Metwally (Tissue and Cell, 2024)

Multi-decadal coastal change detection using remote sensing: the Mediterranean coast of Egypt between El-Dabaa and Ras El-Hekma - Esraa A. El-Masry; Asmaa Magdy; Ayman El-Gamal; Baher Mahmoud; Mahmoud Kh. El-Sayed (Environmental Monitoring and Assessment, 2024)
A key source of information for many decision support systems is identifying land use and land cover (LULC) based on remote sensing data. Land conservation, sustainable development, and water resource management all benefit from the knowledge obtained from detecting changes in land use and land cover. The present study aims to investigate the multi-decadal coastal change detection for Ras El-Hekma and El-Dabaa area along the Mediterranean coast of Egypt, a multi-sectoral development area. Besides, the superiority of the area is highly dependent on its proximity to three development projects: the tourism and urban growth pole at Ras El-Hekma, the beachfront Alamain New Mega City, and the Nuclear Power Plant at El Dabaa. This study utilized multi-spectral Landsat satellite images covering 1990, 2010, and 2020 to perceive the post-classification change detection analysis of the land use and land cover changes (LULCC) over 30 years. The results of the supervised classification from 1990 to 2020 showed a 47.33 km 2 (4.13%) expansion of the agricultural land area, whereas the bare soil land area shrunk to 73.13 km 2 (6.24%). On the other hand, the built-up activities in the area launched in 2010 and escalated to 20.51 km 2 (1.77%) in 2020. The change in land use reveals the shift in the economic growth pattern in the last decade toward tourism and urban development. Meanwhile, it indicates that no conflict has yet arisen regarding the land use between the expanded socioeconomic main sectors (i.e., agriculture, and tourism). Therefore, the best practices of land use management and active participation of the stakeholders and the local community should be enhanced to achieve sustainability and avoid future conflicts. An area-specific plan including resource conservation measures and the provision of livelihood alternatives should be formulated within the National Integrated Coastal Zone Management (ICZM) plan with the participation of the main stakeholders and beneficiaries. The findings of the present work may be considered useful for sustainable management and supportive to the decision-making process for the sustainable development of this area.

Molecular mechanism of empagliflozin cardioprotection in 5-fluorouracil (5-FU)-induced cardiotoxicity via modulation of SGLT2 and TNFα/TLR/NF-κB signaling pathway in rats - Marwa Monier Mahmoud Refaie; Sayed Shehata; Maram El-Hussieny; Michael Atef Fawzy; Nagwa Zenhom Mustafa Ahmed; Heba Marey; Asmaa Mohammed Hishmat; Turki Alkully; Eman Shaaban Mahmoud Abd El Rahman (Toxicological Research, 2024)
One of the commoly used chemotherapeutic agents is 5-Fluorouracil (5-FU). Unfortunately, the clinical administration of 5-FU is complicated with serious cardiotoxic effects and the safe use becomes an urgent task in cardio-oncology. Till now, there are no studies discussed the role of empagliflozin (EMP) against 5-FU cardiotoxicity. Thus, we investigated this effect and the involved mechanisms in 5-FU induced heart injury. Forty male rats of Wistar albino species were used and divided randomly into four groups. Group I is the control group, group II is EMP given group, group III is 5-FU cardiotoxic group and group IV is 5-FU plus EMP group. 5-FU (150 mg/kg) was administered as a single intraperitoneal (i.p.) dose on 1st day to induce cardiotoxicity with or without EMP (30 mg/kg/d) orally for 5 days. The dose of 5-FU is relevant to the human toxic dose. Our data showed that 5-FU given group caused cardiotoxicity with significant increase of serum cardiac enzymes, toll like receptors, enhancement of nuclear factor kappa B (NF-κB), interleukin1β (IL1β), IL6, myeloid-differentiation-factor 88 (MYD88), heart weight, malondialdehyde (MDA), tumor-necrosis-factor-alpha (TNFα), sodium glucose co-transporter 2 (SGLT2), P53 and caspase3 expression with clear histopathological features of cardiotoxicity. Moreover, there is a significant decrease in reduced glutathione (GSH) and total antioxidant capacity (TAC). Interestingly, co-administration of EMP could ameliorate 5-FU induced biochemical and histopathological changes. This effect may be due to modulation of SGLT2, decreasing inflammation, oxidative stress and apoptosis with downregulation of an essential inflammatory cascade that mediates 5-FU cardiotoxicity; TNFα/TLR/NF-κB.

Shoreline displacement along the Mediterranean coast of Egypt between El-Dabaa – Ras El-Hekma - Esraa A. El-Masry; Asmaa Magdy; Baher Mahmoud; Ayman El-Gamal; Mahmoud Kh. El-Sayed (Regional Studies in Marine Science, 2023)

Growth Performance and Biochemical Composition of Desmodesmus sp. Green Alga Grown on Agricultural Industries Waste (Cheese Whey) - Asmaa Salah; Hoda Sany; Abo El-Khair B. El-Sayed; Reham M. El-Bahbohy; Heba I. Mohamed; Ayman Amin (Water, Air, & Soil Pollution, 2023)
Agricultural industries produce vast amounts of liquid waste, which contains a significant concentration of nutrients. In the context of emphasizing the huge increase in population, climate changes, and pollution which results in depletion of fresh water resources, a sustainable solution for a greener future is needed. Wastewater treatment by the use of microalgae can mitigate a part of the problem by restoring water for irrigating agricultural crops. Little studies give insights on the physiological responses and ultrastructure of the Chlorophyta alga Desmodesmus sp. as it grows in cheese whey (CW). The algal strain was mixotrophically grown in a growth medium composed of CW only and CW supported with Bold’s basal medium (BBM) for 14 days. The potent response was observed with algal cultures fed by 15% CW enriched with 50% BBM. Fifteen percent CW in combination with 50% BBM significantly improved Desmodesmus sp. growth (303%), productivity (325%), and accumulation of cell metabolites, mainly lipids (3.89%), and carbohydrates (1.95%). On the contrary, protein and photosynthetic pigment (chlorophyll a , chlorophyll b, and carotenoids) contents were higher in BBM than in all treatments. Fatty acid composition demonstrated that the predominantly accumulated fatty acids were palmitic (25.86%), oleic (35.31%), and linoleic acid (13.22%). In conclusion, Desmodesmus sp. can be a good candidate for phycoremediation when cultivated on CW, whereas it can reduce the nutrition costs and water demand of algal cultivation by 50% and 15%, respectively. Therefore, it may be an effective strategy for algal mass production in sustainable agricultural systems.

Assessment of Water for Different Uses at Some Localities of the Dakhla Oasis, Western Desert, Egypt - Mahmoud H. Darwish; Asmaa G. Sayed; Sedky H. A. Hassan (Water, Air, & Soil Pollution, 2023)

Antioxidant, antiapoptotic, and antifibrotic abilities of L-Arginine ameliorate the testicular dysfunction in diabetic rats - Manal M. Sayed; Nessren M. Abd el-Rady; Walaa M.S. Gomaa; Ahmed Hosny; Asmaa M.S. Gomaa (Tissue and Cell, 2023)

Oxidative Stress and Immunopathological Alterations of Clarias gariepinus Exposed to Monocyclic Aromatic Hydrocarbons (BTX) - Alaa El-Din H. Sayed; Hamdy A. M. Soliman; Shaimaa K. Idriss; Sary Kh. Abdel-Ghaffar; Asmaa A. A. Hussein (Water, Air, & Soil Pollution, 2023)
This study’s goal was to assess the catfish’s response to exposure to monoaromatic petroleum hydrocarbons (benzene, toluene, and xylene) and its recovery after exposure using oxidative stress, histopathological, and immunological changes as biomarkers. Four groups: one as control and other three exposed to benzene (0.762 ng/L), toluene (26.614 ng/L), and xylene (89.403 ng/L), respectively, for 30 days and then recovery period for 30 days. The levels of the cortisol, lipid peroxidation, and cytokines (IL-1β, IL-6) increased significantly ( p < 0.05) after exposure to benzene and xylene compared to control. Superoxide dismutase (SOD), total antioxidant capacity (TAC), and acetylcholinstease (Ach) decreased significantly ( p < 0.05) in fishes exposed to benzene only compared to control group. While glutathione-S-transferase (GST) did not show any change in different treatment groups compared to control group. The histopathological signs of liver exposed to benzene, toluene, and xylene displayed aggregation of melanomacrophages, congestion of sinusoids, vacuolar degeneration of hepatocytes, necrotic area with inflammatory cell infiltration, and thrombus of central vein. Kidney exposed to benzene, toluene, and xylene showed dilatation of Bowman’s space with atrophy of glomerular tuft, lyses of RBCs with mononuclear cell infiltration, multifocal area of hemopoietic tissue necrosis, organized thrombus with perivascular hemorrhage, focal inflammatory cellular reaction, renal tubular necrosis, and thrombus of blood vessels. Spleen exposed to benzene, toluene, and xylene showed hyperplasia of lymphoid follicles in white pulp in a mild degree. These lesions appeared to a mild degree or disappeared completely after recovery period to BTX except spleen. In conclusion, monocyclic aromatic hydrocarbons (BTX) are hazardous to fish and the toxicity level was as benzene > xylene > toluene even though after recovery period.

Emergency vaccination of cattle against lumpy skin disease: Evaluation of safety, efficacy, and potency of MEVAC® LSD vaccine containing Neethling strain - Abdel-Hamid Bazid; Momtaz Wasfy; Mohamed Fawzy; Mohamed Nayel; Mohamed Abdelmegeid; Randa Y. Thabet; Hui Sian Yong; Magdy M. El-Sayed; Asmaa Magouz; Yassien Badr (Veterinary Research Communications, 2023)
Lumpy skin disease (LSD) is an emerging disease of cattle causing significantly high economic losses. Control of LSD depends on the use of homologous attenuated LSD virus strains isolated originally from South Africa (the Neethling strain). The virus belongs to the genus Capripoxvirus , which includes sheep pox virus and goat pox virus. The present study was conducted to evaluate the safety and efficacy of a new live attenuated LSD vaccine produced by Middle East for Vaccines (MEVAC ® ) based on the Neethling strain. Tests were performed both in Egypt and Vietnam. Safety was evaluated by inoculation of five cattle with 10 times the recommended dose and observation of the animals for 14 days. Immunogenicity was tested at different periods post-vaccination (PV) in animals receiving the recommended doses of the vaccine using ELISA and virus neutralization test. Five cows were used to determine the protection index (PI) and non-vaccinated control cattle were included. Three calves were challenged by intradermal inoculation of the wild virus (5 × 10 5 TCID 50 ) 28 days PV. Field or mass vaccination experiments were conducted in Vietnam during national campaigns in the summer of 2021 with 4301 vaccinated animals closely monitored after vaccination. In the field, around 2% (80/4301) of the animals showed hyper-reactivity, and 0.6% (24/4301) showed small skin swellings that disappeared within few hours PV. Abortion was recorded in three animals (0.3% 3/867). Challenged animals were resistant to clinical disease and PI value was 3.5 log 10 . Meanwhile, antibody levels determined by the ELISA were inconsistent among animals and laboratories during the study period. Overall, the findings point to a new safe and effective LSD vaccine.

Trimetazidine alleviates paclitaxel-induced peripheral neuropathy through modulation of TLR4/p38/NF-κB and klotho protein expression - Asmaa S.A. Hammad; Mohamed M. Sayed-Ahmed; Sara Mohamed Naguib Abdel Hafez; Ahmed R.N. Ibrahim; Mohamed M.A. Khalifa; Mahmoud El-Daly (Chemico-Biological Interactions, 2023)

Haemato-biochemical, mutagenic, and histopathological changes in Oreochromis niloticus exposed to BTX - Alaa El-Din H. Sayed; Shaimaa K. Idriss; Sary Kh. Abdel-Ghaffar; Asmaa A. A. Hussein (Environmental Science and Pollution Research, 2023)
The study of the DNA damage response in erythrocytes after exposure to volatile organic compounds (VOCs) can present evidence for its potential effect as genotoxic- biomarkers for environmental pollution. Although VOCs are dangerous pollutants, still little is known about hemotoxic, cytotoxic, and genotoxic effects of such pollutants on fish. We optimized an assay method for apoptosis and DNA damage in erythrocytes of adult tilapia fish after 15 days exposure to benzene (0.762 ng/L), toluene (26.614 ng/L), and xylene (89.403 ng/L). The highest level of apoptosis and DNA damage were recorded in benzene-exposed fish, as was the highest level of histopathological alterations in gills, liver, and kidney. The imbalance of the antioxidants profile explained the stress-case reported in exposed fish. These results suggest that hemotoxic, cytotoxic, genotoxic, and tissue damage were recorded after exposure to BTX in Oreochromis niloticus .

Individual and combined treatments with imidacloprid and spinosad disrupt survival, life-history traits, and nutritional physiology of Spodoptera littoralis - El-Sayed H. Shaurub; Amer I. Tawfik; Asmaa M. El-Sayed (International Journal of Tropical Insect Science, 2023)
The Egyptian cotton leafworm Spodoptera littoralis (Boisduval) (Lepidoptera: Noctuidae) is a pervasive agricultural polyphagous insect pest. Because of the negative side-effects of conventional pesticides used in agricultural fields, safer alternatives for insect pest management are required. We evaluated here susceptibility, biological features, and nutritional indices of S. littoralis after treatment of 4 th -instar larvae with the neonicotinoid imidacloprid and the spinosyn spinosad separately or in combination. Larvae were fed for three successive days on treated leaves of castor-bean Ricinus communis using leaf-dip technique (treatment period). In addition, in case of nutritional indices study, treated leaves were replaced by fresh untreated leaves for two successive days (recovery period). Spinosad was more toxic than imidacloprid, and their combination revealed additive effects based on the co-toxicity factor. Individual and combined treatments significantly decreased pupation rate, adult emergence rate, pupal weight, number of eggs laid per female, egg-hatch, and female longevity, compared to those of controls. Pupal and adult malformations were recorded. During the treatment period, nutritional indices were insecticide- and time-dependent. On the 2 nd day of recovery, all nutritional indices of treated larvae were not significantly different, compared to those of controls. The results presented herein may help in developing more effective crop protection methodologies within integrated pest management of this insect.

Tropaeolum majus L. and low dose gamma radiation suppress liver carcinoma development via EGFR-HER2 signaling pathway - Asmaa I. Owis; Noheir H. Sherif; Asmaa A. Hassan; EL-Moataz Bellah EL-Naggar; Iman H. EL-Khashab; EL-Sayed EL-Ghaly (Natural Product Research, 2023)

Assessment of the potency and effectiveness of a heptavalent oil-adjuvanted (ISA 206) foot-and-mouth disease vaccine in Egypt - Abdel-Hamid Bazid; Haitham M. Amer; Mohamed Nayel; Mohamed Attia; Nada Maklad; Momtaz Wasfy; Mohamed Abdelmegeid; Magdy M. El-Sayed; Asmaa Magouz; Yassien Badr (Archives of Virology, 2023)
Foot-and-mouth disease (FMD) is a serious highly contagious viral disease affecting all cloven-hoofed animals, and outbreaks can have a severe economic impact. An inactivated heptavalent oil-adjuvanted FMD vaccine (Aphtovac-7, MEVAC) was prepared from the foot-and-mouth disease virus (FMDV) strains A-Iran05, A-Africa-IV, O-PanAsia2, O-Manisa, O-EA3, SAT-2 Gharbia, and SAT-2 LIB-12. The vaccine potency and effectiveness were evaluated in three groups of 6- to 8-month-old calves and 200 adult dairy cattle under field conditions. All animals were vaccinated with the vaccine preparation, and the three groups of calves were challenged after 28 days by intradermolingual inoculation with 10 4 50% tissue culture infective dose (TCID 50 ) of FMDV serotype A, O, or SAT-2. Mock-vaccinated calves (two per group) served as unvaccinated controls during the challenge test. Adult dairy cattle were tested for seroconversion using a virus neutralization test at 30, 60, and 120 days post-vaccination. All calves displayed complete protection against challenge with the different serotypes of FMDV when compared to the control groups. Serum samples collected after the primary and booster immunizations at 30 days post-vaccination contained high titers of protective antibodies (≥ 1/32; i.e. 1.5 log 10 ). Antibodies persisted until the end of the study period (120 days), with a peak value around 60 days post-vaccination. The heptavalent FMD vaccine preparation was found to be potent and capable of providing a protective immune response under both experimental and field conditions.

Green synthesis of chitosan/erythritol/graphene oxide composites for simultaneous removal of some toxic species from simulated solution - Asmaa Sayed; Azza M. Mazrouaa; Manal G. Mohamed; Manar El-Sayed Abdel-Raouf (Environmental Science and Pollution Research, 2022)
In this study, chitosan (Ch) is adapted via green methodology including sonication induced crosslinking with different weight ratios of erythritol (Er) from (Ch-Er) 1 to (Ch-Er) 4 . The products were casted in the form of thin films. The chemical modification was proved via FTIR spectroscopy. Then, the modified products were verified via an atomic force microscopy (AFM) investigation for their topography and surface properties. The data revealed that the optimized sample was (Ch-Er) 3 . This sample was further modified by different weight ratios of graphene oxide 0.1, 0.2, 0.4, and 0.8 wt./wt. (symbolized as (Ch-Er) 3 GO 1 , (Ch-Er) 3 GO 2 , (Ch-Er) 3 GO 4 , and (Ch-Er) 3 GO 8 respectively). The prepared samples were investigated by different analytical tools. Then, the adjusted sample (Ch-Er) 3 GO 2 was irradiated by electron beam (e-beam) at 10 and 20 kGy of irradiation doses to give samples (Ch-Er) 3 GO 2 R 10 and (Ch-Er) 3 GO 2 R 20 , respectively. The AFM data of the irradiated samples showed that the pore size decreases, and surface roughness increases at higher energy e-beam due to the formation of more crosslinking points. The optimum samples of the prepared formulations were tested as sorbent materials for simultaneous elimination of methylene blue (MB) dye and mercury cation (Hg 2+ ) from simulated solutions. The maximum removal of both MB dye and Hg 2+ cation was achieved by (Ch-Er) 3 GO 2 R 10 (186.23 mg g −1 and 205 mg g −1 ) respectively. Graphical abstract

Metabolomic profiling and antioxidant potential of three fungal endophytes derived from Artemisia annua and Medicago sativa - Ahmed M. Sayed; Noheir H. Sherif; Ahmed O. El-Gendy; Yara I. Shamikh; Asmaa T. Ali; Eman Zekry Attia; Mo'men H. El-Katatny; Basma Ali Khalifa; Hossam M. Hassan; Usama Ramadan Abdelmohsen (Natural Product Research, 2022)

Retraction Note: Acaricidal and pathogenic effects of the entomopathogenic fungus Beauveria bassiana on engorged females of the fowl tick, Argas persicus (Argasidae) - Asmaa Ali Baioumy; Hamdy Hamed Swelim; Ahmed Adly Ibrahim; Fatma El‑Sayed Mohamed; Aleya Soliman Marzouk; Sherif Helmy El‑Alfy (Experimental and Applied Acarology, 2022)

2, 3-Dimethylsuccinic acid and fulvic acid attenuate lead-induced oxidative misbalance in brain tissues of Nile tilapia Oreochromis niloticus - Wesam A. Neamatallah; Kadry M. Sadek; Yasser S. El-Sayed; Ebeed A. Saleh; Asmaa F. Khafaga (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Acaricidal and pathogenic effects of the entomopathogenic fungus Beauveria bassiana on engorged females of the fowl tick, Argas persicus (Argasidae) - Asmaa Ali Baioumy; Hamdy Hamed Swelim; Ahmed Adly Ibrahim; Fatma El-Sayed Mohamed; Aleya Soliman Marzouk; Sherif Helmy El-Alfy (Experimental and Applied Acarology, 2021)

Dose-Dependent Cardioprotective Effect of Hemin in Doxorubicin-Induced Cardiotoxicity Via Nrf-2/HO-1 and TLR-5/NF-κB/TNF-α Signaling Pathways - Marwa M. M. Refaie; Sayed Shehata; Randa Ahmed Ibrahim; Asmaa M. A. Bayoumi; Seham A. Abdel-Gaber (Cardiovascular Toxicology, 2021)

Prevention of motile Aeromonas septicemia in Nile tilapia, Oreochromis niloticus, using thyme essential oil and its nano-emlusion - Hala Sayed Hassan Salam; Walaa M. S. Mohamed; Sahar Abdel Aleem Abdel Aziz; Asmaa N. Mohammed; Fatma M. M. Korni (Aquaculture International, 2021)

A review article on nanotechnology in aquaculture sustainability as a novel tool in fish disease control - Sameh Nasr-Eldahan; Asmaa Nabil-Adam; Mohamed Attia Shreadah; Adham M. Maher; Tamer El-Sayed Ali (Aquaculture International, 2021)

Ameliorative effects of 9-diaminoacridine derivative against Ehrlich ascites carcinoma–induced hepatorenal injury in mice - Mabrouk Attia Abd Eldaim; Ehab Tousson; Ibrahim El Tantawy El Sayed; Asmaa Zakaria Abd Elmaksoud; Abdullah A. S. Ahmed (Environmental Science and Pollution Research, 2021)

Geo-Environmental Changes and Their Impact on the Development of the Limestone Plateau, West of Assiut, Egypt - Mahmoud H. Darwish; Hanaa A. Megahed; Abd El-Hay A. Farrag; Asmaa G. Sayed (Journal of the Indian Society of Remote Sensing, 2020)

Evaluation of antimicrobial properties of a novel synthesized nanometric delafossite - Mohsen A. Sayed; Asmaa A. H. El-Bassuony; H. K. Abdelsalam (Brazilian Journal of Microbiology, 2020)

Geology and evolutionary stages of the Late Precambrian Hammamat sediments at Gebel Um Tawat, North Eastern Desert, Egypt - Asmaa Adel Khalifa; Hossam Anwer Khamis; Mohamed Mohamed El-Sayed; Mahmoud Hany Shalaby (Arabian Journal of Geosciences, 2020)

Antimicrobial activity of Novel spinel nanoferrites against pathogenic fungi and bacteria - Mohsen A. Sayed; H. K. Abdelsalam; Asmaa A. H. El-Bassuony (World Journal of Microbiology and Biotechnology, 2020)

Role of ATP-Sensitive Potassium Channel (KATP) and eNOS in Mediating the Protective Effect of Nicorandil in Cyclophosphamide-Induced Cardiotoxicity - Marwa M. M. Refaie; Sayed Shehata; Maram El-Hussieny; Wedad M. Abdelraheem; Asmaa M. A. Bayoumi (Cardiovascular Toxicology, 2020)

Factors affecting population dynamics of Tetranychus urticae and its predators on three economic plants in Ismailia, Egypt - Asmaa Mohamed Abdallah; Manal Sayed Mohamed Ismail; Ahmed Hassan AboGhalia; Maha Farid Mohamed Soliman (International Journal of Tropical Insect Science, 2019)

Detection of the intranuclear microsporidian Enterospora nucleophila in gilthead sea bream by in situ hybridization - Nahla Hossameldin Ahmed; Monica Caffara; Ariadna Sitjà‐Bobadilla; Maria Letizia Fioravanti; Angelica Mazzone; Abbass Sayed Aboulezz; Asmaa Mohamed Metwally; Mosaab Adl‐Eldin Omar; Oswaldo R. Palenzuela (Journal of Fish Diseases, 2019)
Enterospora nucleophila is an intranuclear microsporidian responsible for emaciative microsporidiosis of gilthead sea bream (GSB). Its minute size and cryptic nature make it easily misdiagnosed. An in situ hybridization (ISH) technique based on antisense oligonucleotide probes specific for the parasite was developed and used in clinically infected GSB in combination with calcofluor white stain (CW) and other histopathological techniques. The ISH method was found to label very conspicuously the cells containing parasite stages, with the signal concentrating in merogonial and sporogonial plasmodia within the infected cell nuclei. Comparison with CW demonstrated limited ISH signal in cells containing mature spores, which was attributed mostly to the scarcity of probe targets present in these stages. Although spores were detected in other organs of the digestive system as well as in the peripheral blood, proliferative stages or parasite reservoirs were not found in this work outside the intestines. The study demonstrated a frequent disassociation between the presence of abundant spores and the intensity of the infections as determined by the parasite activity. The ISH allows confirmatory diagnosis of GSB microsporidiosis and estimation of infection intensity and will be a valuable tool for a more precise determination of parasite dissemination pathways and pathogeny mechanisms.

Combined QM/MM and Monte Carlo study for redox leveling in Mn and Fe superoxide dismutase - Muhamed Amin; Zainab Mohamed; Mohamed El-Sayed; Asmaa Samy; Afnan Sultan; Mahmoud Bassuoni; Mohamed H. Alkordi (JBIC Journal of Biological Inorganic Chemistry, 2018)

All-trans-retinoic acid ameliorates doxorubicin-induced cardiotoxicity: in vivo potential involvement of oxidative stress, inflammation, and apoptosis via caspase-3 and p53 down-expression - Asmaa F. Khafaga; Yasser S. El-Sayed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Structure–activity relationship investigation of methoxy substitution on anticancer pyrimido[4,5-c]quinolin-1(2H)-ones - Kamel Metwally; Ashraf Khalil; Asmaa Sallam; Harris Pratsinis; Dimitris Kletsas; Khalid El Sayed (Medicinal Chemistry Research, 2013)